Analysis of Statistical Sources on E-Commerce in Armenia - Abgaryan, Davit (Bulletin of Yerevan University G: Economics, 2016)
The article represents the current status of e-commerce in Armenia and the sources of statistics about it. To complement the scarcity of statistical data on ecommerce, the results of the representative survey of Armenian Facebook users are rendered in the article. Based on the scarcity and incompleteness of the statistical data and the importance of e-commerce for the economy, the article substantiates the need of creating a statistical system for e-commerce in Armenia.